2020
DOI: 10.3390/ijerph17093291
|View full text |Cite
|
Sign up to set email alerts
|

Is First Trimester Maternal 25-Hydroxyvitamin D Level Related to Adverse Maternal and Neonatal Pregnancy Outcomes? A Prospective Cohort Study among Malaysian Women

Abstract: Information on the role of 25-hydroxyvitamin D (25(OH)D) in preventing adverse pregnancy/neonatal outcomes is limited in Malaysia. This study aims to determine the relationship between the level of maternal 25(OH)D in the first trimester of pregnant women and their pregnancy/neonatal outcomes. A total of 60 pregnant women in the first trimester were recruited and followed until the end of their pregnancy. The occurrence of any antenatal, delivery, and neonatal complications was recorded. Their blood was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…About nine out of 10 healthy pregnant women in urban Malaysia suffered from vitamin D deficiency throughout their pregnancy. Our findings verified the previous local prevalence studies whereby a high prevalence of vitamin D deficiency was reported in all trimesters ( 1 , 4 , 33 , 34 ). The current study revealed that the prevalence of vitamin D deficiency (25(OH)D <50 nmol/L) was 89.9% in the early pregnancy (≤20 weeks of pregnancy) and 92.2% at late pregnancy (28–40 weeks of pregnancy).…”
Section: Discussionsupporting
confidence: 92%
“…About nine out of 10 healthy pregnant women in urban Malaysia suffered from vitamin D deficiency throughout their pregnancy. Our findings verified the previous local prevalence studies whereby a high prevalence of vitamin D deficiency was reported in all trimesters ( 1 , 4 , 33 , 34 ). The current study revealed that the prevalence of vitamin D deficiency (25(OH)D <50 nmol/L) was 89.9% in the early pregnancy (≤20 weeks of pregnancy) and 92.2% at late pregnancy (28–40 weeks of pregnancy).…”
Section: Discussionsupporting
confidence: 92%
“…The participants assumed that the UVA they are exposed to while driving in the car and sitting by office window (with glasses) might provide them with vitamin D. A previous study done in a Malaysian sub-urban setting among post-menopausal Malay women found that poor knowledge on vitamin D influenced their sun exposure behavior [ 33 ]. The similarity of the findings could be owing to the lack of knowledge regarding vitamin D health benefits compared to other groups of vitamins among both urban and sub-urban females in Malaysia [ 1 , 6 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical evidence of vitamin D deficiency and nonskeletal health is not yet validated [ 5 ]. In countries where dietary vitamin D food intake and supplements are limited [ 6 ], and fortification of food with vitamin D is not compulsory, sunlight exposure is the primary source of vitamin D among the populations [ 6 , 7 ]. Government bodies often establish sun exposure guidelines to ensure a balance between the beneficial and harmful effects of sunlight [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations